Female workers in a transforming economy Women’s labour force participation in Madrid, 1900-1930 - Pallol Trigueros, Rubén (Sociología del Trabajo, 2017)
The article examines women’s opportunities for labour insertion during Madrid´s great socioeconomic transformation in the three first decades of the Twentieth Cen-tury. Women could join the labour force using two new different paths: the one provided by the industrial revolution and the other by an innovative tertiary sector. The industrial jobs remained offering to women such labour conditions that they were at last condemned to the domestic and informal economic. In consequence their social emancipation was restricted. Work in tertiary sector often offered the possibility of that emancipation, even if gender inequality was not eliminated.
Keywords: Labour market; industrialization; tertiary sector; sexual labour segrega-tion; urban history; gender inequality.